Revisiting a dogma: similar survival of patients with small bowel and gastric GIST. A population-based propensity score SEER analysis - Guller, Ulrich; Tarantino, Ignazio; Ulrich, Alexis; Schmied, Bruno; Warschkow, René (Gastric cancer, 2017)
Background: The objective of the present analysis was to assess whether small bowel gastrointestinal stromal tumor (GIST) is associated with worse cancer-specific survival (CSS) and overall survival (OS) compared with gastric GIST on a population-based level. Patients and methods: Data on patients aged 18 years or older with histologically proven GIST was extracted from the SEER database from 1998 to 2011. OS and CSS for small bowel GIST were compared with OS and CSS for gastric GIST by application of adjusted and unadjusted Cox regression analyses and propensity score analyses. Results: GIST were located in the stomach (n = 3011, 59 %), duodenum (n = 313, 6 %), jejunum/ileum (n = 1288, 25 %), colon (n = 139, 3 %), rectum (n = 172, 3 %), and extraviscerally (n = 173, 3 %). OS and CSS of patients with GIST in the duodenum [OS, HR 0.95, 95 % confidence interval (CI) 0.76-1.19; CSS, HR 0.99, 95 % CI 0.76-1.29] and in the jejunum/ileum (OS, HR 0.97, 95 % CI 0.85-1.10; CSS, HR = 0.95, 95 % CI 0.81-1.10) were similar to those of patients with gastric GIST in multivariate analyses. Conversely, OS and CSS of patients with GIST in the colon (OS, HR 1.40; 95 % CI 1.07-1.83; CSS, HR 1.89, 95 % CI 1.41-2.54) and in an extravisceral location (OS, HR 1.42, 95 % CI 1.14-1.77; CSS, HR = 1.43, 95 % CI 1.11-1.84) were significantly worse than those of patients with gastric GIST. Conclusions: Contrary to common belief, OS and CSS of patients with small bowel GIST are not statistically different from those of patients with gastric GIST when adjustment is made for confounding variables on a population-based level. The prognosis of patients with nongastric GIST is worse because of a colonic and extravisceral GIST location. These findings have implications regarding adjuvant treatment of GIST patients. Hence, the dogma that small bowel GIST patients have worse prognosis than gastric GIST patients and therefore should receive adjuvant treatment to a greater extent must be revisited.